Planning physical activity and its benefits in people over 60 - Gałuszka, Aleksandra (Journal of Education, Health and Sport, 2022)
Human aging is a natural, irreversible process causing changes in each of the human body systems. It involves a gradual increase in changes at the biological, psychological and social levels. As a result of these complex and at the same time irreversible natural processes, regenerative and psychophysical capabilities of the human organism weaken, which are additionally limited by illnesses or injuries experienced during life. People in geriatric age have different physical and mental abilities, and the occurring mental and motor deficiencies force the individual ordering of exercises adapted to the general health condition of the patient and the period of disease. The multitude of available forms of exercise makes it possible to tailor exercises to specific needs. Secondary and tertiary prevention, i.e. adherence to current principles in the treatment of the primary disease entity and co-morbidities, becomes an important issue in the elderly and those suffering from ailments. Physical activity in elderly people should affect areas such as endurance, strength, balance, flexibility. It is important to choose activities that are feasible and enjoyable in relation to the disease in question.